ITCHAN-KALA: OPEN-AIR MUSEUM - Mirzaeva , Munira Ilxomovna (INTERNATIONAL CONFERENCES, 2023)
Itchan Kala is the walled inner town of the city of Khiva, Uzbekistan. Since 1990, it has been protected as a World Heritage Sit Notable buildings in Itchan Kala are Juma Mosque, Ak Mosque, madrasahs of Alla-Kulli-Khan, Muhammad Aminkhon, Muhammad Rakhimkhon, Mausoleums of Pahlavon Mahmoud, Sayid Allavuddin, Shergozikhon as well as caravanserais and markets.